A new control scheme for limiting the compensation current and prioritizing power injection in multifunctional grid-connected photovoltaic systems - Ricsa Alhassane Soumana; Michael Juma Saulo; Christopher Maina Muriithi (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2022)
Several recent studies have demonstrated the benefits of incorporating auxiliary functions such as power quality enhancement services in the control strategy of grid-connected photovoltaic (PV) systems. However, most studies ignore the necessity to prioritize the PV power injection into the grid, the primary role of grid-connected PV systems, and limit the compensation (the achievement of the auxiliary functions) according to the available capacity of the PV inverter. Limiting the inverter's rated capacity in terms of maximal current is crucial not only for preserving the life of the semiconductors but also for ensuring the inverter's principal role of injecting active power into the network. This paper proposes a control technique in abc reference frame that incorporates a current harmonics filtering function for two-stage grid-connected PV systems. The proposed strategy inherently prioritizes the PV power injection over current harmonics filtering. It also considers the PV inverter's rated capacity by characterizing it by its peak rated current to fulfil its two functions without exceeding the inverter limit by optimally limiting the current for harmonics compensation. In addition, a fuzzy logic-based control scheme was proposed for the need to limit the generated PV power regardless of environmental conditions. Furthermore, A comparison between the proposed control sheme and a traditional shunt active power filter (APF) in terms of grid current THD improvement was conducted under two scenarios using MATLAB/Simulink. The simulation of the first investigated scenario, where the local load demand power is less than the PV power generation, results in a grid current THD of 3.41% vs. 3.53% when applying the proposed technique and the shunt APF, respectively. In the second scenario, When the load is supplied by the grid and the PV generator, A grid current THD of 2.04% vs 5.54% are obtained using the proposed method and the shunt APF, respectively.